Take time to “paws”: a quality improvement project utilizing facility dogs for staff support - Brittany Reed; Janet Sellers; Kimberly Russell; Kathryn Russell; R. Elyse Heidelberg (Academia Mental Health & Well-Being)
Supporting the resilience and well-being of frontline nursing staff and medical professionals is critically important. This quality improvement project aimed to assess the impact of facility dog visits on the well-being of frontline nursing staff and medical professionals, both individually and at the unit level. Over three months, facility dogs, their handlers, and members of the staff resilience team visited outpatient and inpatient nursing areas, engaging staff in brief interactions. Surveys were administered to participants before visit (pre-visit), immediately after visits, and post-visit. These surveys assessed demographic information, individual mood, and perceived unit mood. Response to the visits was captured through immediate and post-visit surveys, while burnout was evaluated in pre- and post-visit surveys. Open-ended comments were also elicited from respondents. Overall, 87 unit visits were conducted, involving over 500 hematology or oncology frontline healthcare professionals, and 792 surveys were completed across three timepoints. Most respondents identified as inpatient nurses. Immediately following facility dog visits, more than 90% of respondents reported improved individual and unit mood, and over 70% reported sustained improvements in unit mood in the post-visit survey. Respondents’ comments reinforced the benefits of facility dog visits for staff wellness and resilience. Facility dog visits promote the well-being of pediatric hematology/oncology nurses, both individually and at the unit level, and should be scheduled regularly and frequently. This project highlights the importance of supporting the well-being of healthcare professionals and is relevant for individual healthcare professionals, the institutions they serve, and the patients under their care.